1979
DOI: 10.1139/o79-006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phalloidin on actin proteolysis as measured by viscometry and fluorimetry

Abstract: Even at low concentration, phalloidin shows a marked protection of F-actin against the action of trypsin or pronase. G-actin is not protected at any concentration of phallodin. The kinetics of the proteolysis show that a change in the environment of tryptophan residues is preceded by disruption of the filamentous structure of F-actin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…While the interaction of phalloidin and F-actin does produce an ultraviolet difference spectrum, it was not possible to detect a conformational change in F-actin-phalloidin mixtures by the method of susceptibility to proteolytic digestion because such mixtures do not show a measurable rate of digestion. This lack of digestbility of phalloidin-stabilized actin, compared with the measurable rate of digestion of F-actin in the absence of phalloidin (Figure 4; Rich & Estes, 1976), has been also reported by other investigators (deVries & using different enzymes (Pollender & Gruda, 1979). These findings could be evidence that a conformational change occurs in actin upon binding phalloidin.…”
Section: Discussionsupporting
confidence: 84%
“…While the interaction of phalloidin and F-actin does produce an ultraviolet difference spectrum, it was not possible to detect a conformational change in F-actin-phalloidin mixtures by the method of susceptibility to proteolytic digestion because such mixtures do not show a measurable rate of digestion. This lack of digestbility of phalloidin-stabilized actin, compared with the measurable rate of digestion of F-actin in the absence of phalloidin (Figure 4; Rich & Estes, 1976), has been also reported by other investigators (deVries & using different enzymes (Pollender & Gruda, 1979). These findings could be evidence that a conformational change occurs in actin upon binding phalloidin.…”
Section: Discussionsupporting
confidence: 84%
“…It is well known that proteins most susceptible to in vitro proteolysis have short in vivo half-lives [34]. Thus, the experiments of Pollender and Gruda [37] offer strong supportive evidence to ours that the major mechanism by which phalloidin induces increases in liver actin content in vivo is by inhibiting actin degradation.…”
Section: Discussionsupporting
confidence: 60%
“…Pollender and Gruda [37] have shown that phalloidin protects actin against trypsin-or pronase-induced proteolysis in vitro. It is well known that proteins most susceptible to in vitro proteolysis have short in vivo half-lives [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the polymer of intact actin, these sites, all located in subdomain 2 of the monomer [2][3][4], are protected. Proteolysis by subtilisin and trypsin was, however, observed at high enzyme concentrations [31,32]. It seemed to be of particular interest to investigate the effects of removal of the C-terminal residues on the accessibility of the cleavage sites within the surface loop 39-51 in F-actin, since, according to the atomic model of the actin filament [1], this loop is directly involved in the inter-monomer interaction with the C-terminal phenylalanine.…”
Section: Polymerization Properties Of Intact and C-terminal Truncatedmentioning
confidence: 99%